2018
DOI: 10.1007/s00167-018-5321-8
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage repair surgery prevents progression of knee degeneration

Abstract: Purpose To investigate, whether cartilage repair surgery for focal osteochondral defects at the knee results in less degenerative changes over 6 years in a MR imaging follow-up than morphologically initially identical defects in non-operated control subjects from the osteoarthritis initiative (OAI). Methods A total of 32 individuals received baseline and follow-up MRI. In n = 16 patients with cartilage repair [osteochondral autograft transfer system (OATS), n = 12; spongiosa-augmented matrix-associated autolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 57 publications
(94 reference statements)
0
37
0
3
Order By: Relevance
“…Articular cartilage damage is regarded as a significant cause for early OA in adolescents and young adults 2. The implantation of a scaffold or cartilage repair surgery represents a good choice after failure of conservative treatment for early OA patients 3, 4. Under normal nutritional conditions, there is a dynamic balance of anabolic and catabolic activities of chondrocytes, which mainly depend on glycolysis to supply their basic energy requirements 5.…”
Section: Introductionmentioning
confidence: 99%
“…Articular cartilage damage is regarded as a significant cause for early OA in adolescents and young adults 2. The implantation of a scaffold or cartilage repair surgery represents a good choice after failure of conservative treatment for early OA patients 3, 4. Under normal nutritional conditions, there is a dynamic balance of anabolic and catabolic activities of chondrocytes, which mainly depend on glycolysis to supply their basic energy requirements 5.…”
Section: Introductionmentioning
confidence: 99%
“…5 In contrast to microfracture, restoration procedures produce cartilage that more closely resembles natural hyaline cartilage. 7 These newer generation techniques have been shown to provide durable cartilage restoration, slow the progression of degenerative joint changes, and result in high return rates to preinjury level of play. 789 Despite this, in an analysis from 2004 to 2011, McCormick et al showed that palliative procedures were the most commonly utilized cartilage procedures in the United States during that time interval.…”
mentioning
confidence: 99%
“…The current review of various techniques and studies revealed encouraging results. Jungmann et al [3] (2019) did a prognostic Level II study comparing the progression of osteoarthritis in 16 patients treated with cartilage repair surgery for the focal chondral defects (osteochondral autograft transplant system [OATS] n = 12; membrane based autologous chondrocyte implantation [MACI], n = 4) with similar non-operated 16 subjects from osteoarthritis initiative study group having identical cartilage defects. The chondral defects in both the groups were equally distributed at the femoral condyles (n = 8) and the patella (n = 8) and the mean defect size was 1.4 cm 2 (SD ± 1.3) and 1.3 cm 2 (SD ± 1.2) for the control and the cartilage repair groups, respectively.…”
Section: Rationale Behind Cartilage Repair Surgeriesmentioning
confidence: 99%